COMPULSIVE BUYING : TINJAUAN PEMASAR DAN PSIKOLOG - Titin Ekowati (SEGMEN Jurnal Manajemen dan Bisnis, 2009)
The study of consumer behavior that related with individual charachteristic is compulsivebuying. Individual who doing it called compulsive buyer. The condition have related tomarketing and psichologycal science. Based on marketer compulsive buying is favorablecondition and profitable to the company. But based on psycholog the fenomena is notfavorable. Because it create stress condition, depression and financial distress forindividual.Key word : Compulsive buying, marketer, psicholog